Using milk flow rate to investigate milk ejection in the left and right breasts during simultaneous breast expression in women - Trengove Naomi J; Robert Marc; Spatz Diane L; Geddes Donna T; Prime Danielle K; Hartmann Peter E (BMC, 2009)
Abstract Background Milk ejection is essential for a successful lactation, however techniques to measure milk ejection in women are often complex and invasive. Recent research has demonstrated that at milk ejection, milk duct diameter increased in the breast (measured by ultrasound) at the same time as milk flow rate increased (measured using a weigh balance). This study aimed to evaluate a purpose-built continuous weigh balance (Showmilk, Medela AG) to measure changes in milk flow rate from the breast to identify milk ejections during milk expression. In addition, the Showmilk was used to determine if milk ejection occurred simultaneously in both breasts during double pumping. Methods Increased milk flow rates during single pumping were compared to simultaneous ultrasound measurements of increased milk duct diameters in 14 mothers. In addition, increases in milk flow rate were compared between the left and right breasts of 28 mothers during double pumping for 15 minutes with two separate electric breast pumps attached to two Showmilks to record milk flow rate. Results Increased milk flow rates were associated with increased milk duct diameters during single pumping. The mean number of milk ejections was not different between the Showmilk (4.2 ± 2.0) and ultrasound (4.5 ± 1.5) techniques. Overall, 67 milk ejections were measured and of these, 48 (72%) were identified by both techniques. The left and right breasts responded synchronously with 95.5% of the flow rate increases corresponding between the breasts. The mean number of milk ejections identified by an increase in milk flow rate during double pumping was 5.1 ± 1.7 and 5.0 ± 1.7 for the left and right breasts, respectively. In addition, mothers chose the same expression vacuum for the left (-198 ± 31 mmHg) and right (193 ± 33 mmHg) breasts. Conclusion The Showmilk can simply and non-invasively record milk ejections by measuring increases in milk flow rate that correspond with increases in milk duct diameter. For the first time measurement of milk flow rate has been used to confirm that milk ejections occur simultaneously in the left and right breasts during double pumping. The use of the Showmilk will facilitate further research into the relationship of milk ejection and milk removal.